The APA 7th: learning and application difficulties - Neubauer, Adrián; Hernaiz-Sánchez, Ariadna (Frontiers in Education, 2025)
BackgroundEducational institutions promote the development of writing in students, a fundamental competence in higher education, where they face challenges such as discursive genres and academic standards, especially in citation. Many undergraduates are unfamiliar with APA standards, which leads to common errors and frustration, although initiatives such as workshops and feedback have been shown to be effective in improving their learning.AimThis study aims to assess students’ knowledge of APA 7th and to identify common errors in applying it.MethodologyTwo questionnaires with 20 questions each were designed and administered to 70 students before and after providing asynchronous resources. The results indicate a low overall knowledge of APA 7th among students.FindingsUndergraduates are found to be more proficient in indirect citations, tables and figures, but less proficient in literal citations and bibliographic references. Asynchronous resources did not have a significant influence on improving the learning of the standards, although there was a slight improvement in the results.ValueIt is concluded that it is crucial to reinforce the teaching of APA 7th standards through specific initiatives, such as workshops or assessment rubrics, coinciding with previous studies that highlight this need.